RADI-19. DIFFUSION KURTOSIS IMAGING CAN HELP DIFFERENTIATE LOW- AND HIGH-GRADE GLIOMAS IN PEDIATRIC PATIENTS WITH SPECIFIC LOCATION-RELATED PATTERNS: A PROSPECTIVE SINGLE CENTRE STUDY - Voicu, Ioan Paul (Neuro Oncol, 2018)
PURPOSE: To investigate whether diffusion kurtosis imaging (DKI) differentiates pediatric low- and high-grade midline and hemispheric gliomas (mLGG, mHGG, hLGG and hHGG). MATERIALS AND METHODS: After obtaining informed consent, fourteen children (median age 7.4 years, 8 males) with midline gliomas and eighteen children (median age 9.6 years, 9 males) with hemispheric gliomas were prospectively studied on a 3T magnet. Conventional and DKI sequences (30 directions, 3 b values: 0, 1000, 2000) acquired with simultaneous multislice technique (SMS) were obtained. Mean kurtosis (MK), axial kurtosis (AK), radial kurtosis (RK) and fractional anisotropy (FA) values were calculated. The enhancing and nonenhancing tumor volumes (VOIs) were segmented semiautomatically. Mean and highest 20 percentile (H20%) DKI values in tumor VOIs were calculated for each metric. Differences among DKI values in the enhancing and nonenhancing VOIs between LGG and HGG of each group were assessed with an independent sample t-test. RESULTS: After excluding three patients for artifacts, the scans of twelve children (8 mLGG and m4 HGG) with midline gliomas and seventeen children (12 mLGG and 5 mHGG) with hemispheric gliomas were analysed. In midline gliomas, significantly different H20% FA, mean MK, H20% MK, mean AK and H20% AK values were found in the nonenhancing tumor VOI (p<0.05, p<0.008, p<0.007, p<0.045 and p<0.001respectively). In hemispheric gliomas, significantly different mean RK, H20%RK, mean MK and H20% MK values were found in the enhancing tumor VOI (p<0.003, p<0.007, p<0.004 and p<0.001 respectively). CONCLUSIONS: DKI can help differentiate low and high-grade gliomas in pediatric patients with location-related patterns.